Fibroblast Growth Factor Signaling Pathway in Endothelial Cells Is Activated by BMPER to Promote Angiogenesis. Issue 2 (February 2015) - Esser, Jennifer S.; Rahner, Susanne; Deckler, Meike; Bode, Christoph; Patterson, Cam; Moser, Martin
<x xml:space="preserve">Abstract</x> Objective— Previously, we have identified bone morphogenetic protein endothelial cell precursor–derived regulator (BMPER) to increase the angiogenic activity of endothelial cells in a concentration-dependent manner. In this project, we now investigate how BMPER acts in concert with key molecules of angiogenesis to promote blood vessel formation. Approach and Results— To assess the effect of BMPER on angiogenesis-related signaling pathways, we performed an angiogenesis antibody array with BMPER-stimulated endothelial cells. We detected increased basic fibroblast growth factor (bFGF/FGF-2) expression after BMPER stimulation and decreased expression of thrombospondin-1. Additionally, FGF receptor-1 expression, phosphorylation, FGF signaling pathway activity, and cell survival were increased. Consistently, silencing of BMPER by small interfering RNA decreased bFGF and FGF receptor-1 expression and increased thrombospondin-1 expression and cell apoptosis. Next, we investigated the interaction of BMPER and the FGF signaling pathway in endothelial cell function. BMPER stimulation increased endothelial cell angiogenic activity in migration, Matrigel, and spheroid assays. To block FGF signaling, an anti-bFGF antibody was used, which effectively inhibited the proangiogenic BMPER effect. Accordingly, BMPER-silenced endothelial cells under bFGF stimulation showed decreased angiogenic activity compared with bFGF control. We confirmed these findings in vivo by subcutaneous Matrigel injections with and without bFGF in C57BL/6_Bmper+/− mice. Aortic ring assays of C57BL/6_Bmper+/− mice confirmed a specific effect for bFGF but not for vascular endothelial growth factor. Conclusions— Taken together, the proangiogenic BMPER effect in endothelial cells is mediated by inhibition of antiangiogenic thrombospondin-1 and enhanced expression and activation of the FGF signaling pathway that is crucial in the promotion of angiogenesis.